2003
DOI: 10.1016/s0002-9440(10)63801-1
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of EMAP II by Hypoxia

Abstract: Endothelial-monocyte-activating polypeptide II (EMAP II) is a proinflammatory cytokine and a chemoattractant for monocytes and granulocytes. We have previously shown that EMAP II mRNA is strongly expressed at sites of apoptosis in the mouse embryo and that the mature protein is cleaved from its cellular precursor (proEMAP II/p43) by caspase activation to become released from cells. Here we demonstrate in vivo that EMAP II mRNA expression is strongly increased in tumor necrosis factor alpha (TNF)-treated murine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 30 publications
(35 reference statements)
1
50
0
2
Order By: Relevance
“…Hypoxia induces the expression of VEGF, EMAP-II, endothelin, SEMA3A, SDF1α, eotaxin, and oncosatin M, thus explaining the enhanced availability of these factors within oxygen-deprived regions (19,(44)(45)(46)(47)(48)(49). The cytokine-rich tumor microenvironment further provides factors such as CCL2, CCL5, or CSF1 produced by many different cell types such as tumor cells, fibroblasts, endothelial cells, or TAMs themselves (43).…”
Section: Tumor Hypoxiamentioning
confidence: 99%
“…Hypoxia induces the expression of VEGF, EMAP-II, endothelin, SEMA3A, SDF1α, eotaxin, and oncosatin M, thus explaining the enhanced availability of these factors within oxygen-deprived regions (19,(44)(45)(46)(47)(48)(49). The cytokine-rich tumor microenvironment further provides factors such as CCL2, CCL5, or CSF1 produced by many different cell types such as tumor cells, fibroblasts, endothelial cells, or TAMs themselves (43).…”
Section: Tumor Hypoxiamentioning
confidence: 99%
“…In the cytoplasm, AIMP1 helps the catalytic reaction of arginyl-tRNA synthetase. Recently, it has been demonstrated that AIMP1 is secreted as a result of various stimuli, including TNF-␣, heat shock, and hypoxia (13)(14)(15), and that it acts as a multifunctional cytokine on both endothelial and immune cells (16 -19). …”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…It appears that TAMs may be recruited to these hypoxic sites by the release of macrophage chemoattractants by hypoxic tumor and other stromal cells. These include VEGF, 25 endothelin-2 26 and EMAPII, 27 which are upregulated by hypoxic tumor cells. It is also likely that, as TAMs are phagocytic scavenger cells, they will be attracted by signals released by apoptotic tumor cells, cell debris from necrosis, or constituents released by the local extracellular matrix (ECM) as tumor cells undergo necrosis.…”
Section: Monocyte Recruitment Into Tumorsmentioning
confidence: 99%